The Road to Bisacyldigermanes: A New Compound Class Suitable as Visible Light Photoinitiators. Issue 9 (31st May 2022) - Wiesner, Tanja; Glotz, Gabriel; Wunnicke, Odo; Bleger, David; Knezevic, Ivana; Torvisco, Ana; Fischer, Roland C.; Kelterer, Anne‐Marie; Gescheidt, Georg; Haas, Michael
Abstract: In this contribution we present a novel synthetic procedure towards a variety of bisacyldigermanes via the Corey‐Seebach approach. All isolated compounds were characterized by NMR spectroscopy, mass spectrometry and X‐ray crystallography. The target compounds were further analyzed via UV/Vis absorption spectroscopy and their longest wavelength absorptions were assigned by DFT calculations. Moreover, we determined the activity of our new photoinitiators by photolysis experiments (photobleaching). Additionally, CIDNP spectra confirmed the radical pathway of the investigated compounds. Abstract : A series of bisacyldigermanes were synthesized via the Corey‐Seebach approach via an easily accessible digermane synthon. By testing their performance as photoinitiators, we found high activities as well as good photobleaching even at 430 nm.